Distribución espacial del Alouatta Seniculus “coto mono” y su relación con los recursos disponibles en el área de conservación municipal Asociación Hídrica Aguajal Renacal del Alto Mayo. - Vásquez Ruiz, Elsa (2005)
The present thesis “space Distribution of the groups of Alouatta seniculus “Boundary monkey” and its relation with the resources available in Hydric association Aguajal Renacal of the Alto Mayo” was made with Vegetal species that use for their feeding in the area of reserve Aguajal Renacal of the High May besides to contribute to elaborate the proposal handling plan. The study was divided in two zones: the Humid zone (the Island) and the Dry Zone (Renacal); the pursuit of the groups of Alloutta seniculus in the humid zone was made in the month of December the methodology used in this zone was: transecto, method that consists of which one or more observant they cross the transectos (way trails, rivers), generally straight at a continuous speed and stopping every certain stretch, I am used like transecto the Avisado river, this methodology complemented with the direct observation of the behavior of the Observant species –animal once sighted the species it was come to the filling of the registry leaf in which it is written, hour of the day, distances of the canoe, altitude, number of adults height in the trees, activity and feeding, attitude, displacement, among others. The evaluation of the species in the dry zone I am made in the month of June, at time of summer that allowed to the entrance to the given Renacal the topographic characteristics of this zone. The methodology applied in this zone was: Observant animal. In it is area was not the species in study but it was observed other species such as: Saimiri sciurensis, Cebus apella feeding on white Oje Ficus anthelminticus.It is recommended, are made long term studies, to know the distribution the groups of A. Seniculus in the Aguajal Renacal. And the implementation of voluntary military service of foresters people in charge to monitorear and to protect the activities within the zone of Reserve.